Fighting Social Exclusion: Institutional change and its impact on the poor and excluded: The Indian decentralisation experience - D. Narayana (OECD Development Centre International Labour Office, 2005)
This study analyses the impact of democratic decentralisation on the chances of social excluded groups to participate in newly created local governance institutions Panchayat Rai Institutions - in three Indian states. This institutional reform included a quota for disadvantaged groups like women, lower casts and the poor to ensure their effective participation. The comparative analysis on the determinants of participation of these groups vis--vis other groups across the states of Kerala, Tamil Nadu and Madhya Pradesh yields highly interesting results, relevant beyond the Indian context. First, the outcomes of decentralisation on participation are different across states and within different marginalised groups. While in Kerala socially disadvantaged groups and the poor are at least as represented as other groups at the Panchayat level, in Tamil Nadu and Madhya Pradesh they continue to be largely under-represented. Secondly, creating awareness through political mobilization seems to be the driving factor explaining the different outcomes across the three states. In fact, Kerala distinguished itself from the other two states significantly with respect to mobilization possibilities through political parties, a denser network of self-help groups, better outcomes in basic education and literacy. From the findings of this study one can conclude that the success of institutional reforms aiming to increase political participation depend on the specific design of the process itself as well as on the local conditions. An effective devolution of resources to Panchayats seems to positively influence participation as well as a vibrant political society characterized by a broad spectrum of political parties, active civil society and newspaper reading.